Hydrocarbon generation and expulsion modeling of different lithological combination source rocks from the Funing Formation in the Subei Basin - Peng, Jinning; Li, Longlong; Du, Chongjiao; Liu, Xu; Zhu, Jianhui; Liang, Shiyou; Qiu, Qi; Wang, Dongyan (Frontiers in Earth Science, 2023)
The oil expulsion efficiency and retention efficiency of shale affect the enrichment and preservation of shale oil. Two series of semi-closed hydrous pyrolysis experiments were performed under in situ geological conditions on Paleogene shale sample as comparable analogue to evaluate the generation and preservation potential of shale oil in the Funing Formation shale in the Subei Basin. The results show that: 1) The oil-generation capacity evolution of different lithological combinations source rocks in the Funing Formation of Subei Basin can be roughly divided into four stages a) relatively slow oil-generating and slow gas-generating b) relatively fast oil-generating and slow gas-generating c) oil cracking into gas and d) kerogen cracking into gas; 2) Different lithological combinations have different hydrocarbon generation, expulsion and retention efficiency: total oil generation rate and gas generation rate of pure shale are higher than which of shale with silty interlayer, the exchange point between the oil expulsion rate and retention rate of pure shale is earlier than which of shale with silty interlayer indicates that the pure shale experienced the expulsion and retention process earlier. The oil retention mainly occurs at the EqVRo of 0.84%-1.12%, while the oil is mainly discharged to the adjacent siltstone at EqVRo of 1.12%-1.28%. Based on the simulation under geological conditions, it is recognized that for shale oil exploration in Subei Basin, the favorable thermal maturity is at EqVRo of 0.84% to 1.12%, and the favorable lithology is the shale with silty interlayer. On the one hand, the siltstone interlayer can provide pore space for the early generated oil, and the concentration difference of hydrocarbons between the shale and the interlayer can be formed, so that the generated shale can continuously enter the interlayer, On the other hand, the shale above the interlayer can be used as a cap rock to preserve shale oil. The favorable area for shale oil exploration in Subei Basin is the area with relatively high maturity (at VR value of about 1.1%).